Factors Associated with the Appropriate Use of Asthma Drugs - Marie-Sophie Jobin; Jocelyne Moisan; Yves Bolduc; Eileen Dorval; Louis-Philippe Boulet; Jean-Pierre Grégoire (Canadian Respiratory Journal)
BACKGROUND: When used properly, asthma drugs can reduce asthma-related morbidity and mortality.